Pemberdayaan Masyarakat Melalui Pelatihan Bangunan Stil Bali Bersama Mitra Tori Kreasi Art and Home Décor di Desa Singapadu Tengah, Gianyar - I Wayan Parwata; Lilik Antarini; I Nyoman Sutapa; I Nyoman Pande Jasminata Putra; I Wayan Khresna Adhi Guna P (Postgraduated Community Service Journal, 2025)
Singapadu Tengah Village is an arts village located in Sukawati District, Gianyar Regency. The residents of Singapadu Tengah Village primarily work as artists, farmers, and in the tourism sector. The arts include dance, painting, batik, sculpture, carving, and architecture. The village's architectural arts have flourished since the 1970s, particularly in the areas of carpentry and traditional Balinese structures (Balinese style), with their woodwork and carving components. In the 1980s, Balinese style buildings gained popularity in line with economic and tourism growth. However, since 2022, demand has increased but has been hampered by a decline in the workforce in the Balinese steel and carving sectors. The problem is that the younger generation prefers to work in the tourism sector rather than continuing their skills as builders (undagi). The decline in the number of undagi has resulted in sacred buildings such as pelinggih and other sacred buildings being built by non-Hindu craftsmen, who do not have taksu (spiritual charisma), and do not understand ritual procedures such as melaspas, and measuring the physical and spiritual quality of Balinese buildings to be generic and not have taksu according to the local characteristics of each village.The purpose of this community service activity is to direct the younger generation to develop creativity and make a source of livelihood from traditional building work, starting from the size (dimension), layout, woodwork relating to the structural and construction work of the building, carving work, sanding, varnishing, and pepalihan pairs on Balinese buildings. The method of implementing the activity includes socialization, training and strengthening the younger generation in the form of creative groups and communities, and the implementation of ergonomic work models in the field of Balinese style buildings, so that the younger generation plays a role and actively works and participates in preserving Balinese culture. From the training activities that have been carried out, the interest of young people from Sukawati State Vocational High School III and young people in the Singapadu Tengah village environment is enthusiastic about participating and developing this activity. They are generally interested in developing this Balinese building business.